1998
DOI: 10.1111/j.1574-6968.1998.tb12896.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of antimicrobial action of indolicidin

Abstract: Indolicidin, a 13-residue antimicrobial peptide isolated from cytoplasmic granules of bovine neutrophils, exhibits activity against Gram-positive and Gram-negative bacteria as well as fungi. Although indolicidin is bactericidal and permeabilizes the bacterial membranes, it does not lyse the bacterial cells. We examined the effect of bactericidal concentrations of indolicidin on the morphology of Escherichia coli cells and found that it induces filamentation. Further investigations showed that indolicidin inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
226
0
6

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(237 citation statements)
references
References 23 publications
5
226
0
6
Order By: Relevance
“…(2) Although the average rmsf of the peptide backbone was only slightly higher for W11A than for IND, the average rmsf of residues 8-13 is significantly higher while the average rmsf of residues 1-5 is slightly lower in W11A than in IND. These data indicate that loss of the boat-shaped structure of W11A in DPC is driven by a disordering of residues [8][9][10][11][12][13]. (3) The orientation of the tryptophan side chains had a greater average fluctuation in W11A than for indolicidin in DPC.…”
Section: Results From the W11a Mutant Simulationmentioning
confidence: 88%
“…(2) Although the average rmsf of the peptide backbone was only slightly higher for W11A than for IND, the average rmsf of residues 8-13 is significantly higher while the average rmsf of residues 1-5 is slightly lower in W11A than in IND. These data indicate that loss of the boat-shaped structure of W11A in DPC is driven by a disordering of residues [8][9][10][11][12][13]. (3) The orientation of the tryptophan side chains had a greater average fluctuation in W11A than for indolicidin in DPC.…”
Section: Results From the W11a Mutant Simulationmentioning
confidence: 88%
“…However, no morphological changes to the septa were observed with TEM. The peptides PR-39 [29], PR-26 [29], indolicidin [31] and microcin [28] were previously found to cause filamentation which may be caused by the inhibition or alteration of membrane proteins required for septum formation [4]. Sochaki and colleagues previously found that fluorescently labeled LL-37 more readily entered E. coli cells at the septal regions of dividing cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms by which proteolytic activity could cause this replication defect include damaging bacteria directly and activating cationic antimicrobial peptides (28). We tested the hypothesis that a cathelicidin mediates Salmonella filamentation within macrophages because a synthetic active peptide of indolicidin, a bovine cathelicidin, has been reported to induce bacterial filamentation in vitro (29). Mice produce a single cathelicidin, named CRAMP.…”
Section: Intracellular Protease Activity Mediates Impaired Salmonellamentioning
confidence: 99%